Aspergillosis after liver transplantation in the context of common variable immunodeficiency: case report. Issue 5 (15th May 2013) - Chen, Y.; Cameron, A.
Abstract: Common variable immunodeficiency (CVID) is the most common primary immune defect, resulting in hypogammaglobulinemia as well as deficits in cell‐mediated immunity. Although it mainly manifests in immunodeficiency and related infection, CVID can also be associated with autoimmune phenomena such as immune thrombocytopenic purpura, hemolytic anemia, rheumatoid arthritis, lupus, primary biliary cirrhosis, and autoimmune hepatitis (AIH). AIH is a less common but serious complication of CVID, which can result in early cirrhosis, ascites, and even hepatocellular carcinoma. Here, we discuss a recent case of transplantation for cirrhosis secondary to AIH in the context of CVID. Although the patient's surgery occurred without complication, he rapidly developed fulminant alveolar hemorrhage and seizures, and died secondary to disseminated neuroaspergillosis.